Experiment investigation of turbulence generated by solitary wave over smooth beds - Winarta, Bambang; Nadiatul Adilah, Ahmad Abdul Ghani; Tanaka, Hitoshi; Yamaji, Hiroto; Mohammad Fadhli, Ahmad (Asian Research Publishing Network (ARPN), 2016)
Two cases of solitary motion experiment have been conducted over smooth beds by using solitary wave generation system facilitated by two types of rotating disk, th e detail explanation about these rotating disks can be found in the former publication (Tanaka et al. 2011). In the present study, a deep analysis has been done to verify the sufficiency of tranquil period between two peaks of “solitary-wave-like” motion in turbulent flow regime and also to validate the reliability or sensitivity of ensemble averaging to 50 wave numbers produces by continuous measurement. The analysis results show that the minimum number of “periodical” or continuous wave measurement to attain reliable ensemble average is 45 wave numbers for case of turbulent solitary motion with Reynolds number (Re) = 7.34 x 105.